A ritual geology : gold and subterranean knowledge in Savannah West Africa - D'Avignon, Robyn, 1984- (Duke University Press, 2022)
"One of the first accounts of the politics of geological research in colonial and post-colonial Africa, Ritual Geology models a new regional approach to African history and ethnography centered on geology. Rooted in the goldfields of Senegal, A Ritual Geology carries the reader across the goldfields of Guinea, Mali, Cote d'Ivoire and Burkina Faso from the medieval past into the present-day. Weaving together archival and ethnographic work among geologists, bureaucrats, artisanal miners, politicians, and ritual authorities, Robyn d'Avignon centers African orpailleurs as intellectual actors, upending narratives that treat miners in the global south as workers and victims of land alienation. Across these periods, A Ritual Geology presents sustained accounts of the central role of African mining expertise in geological exploration in colonial and post-colonial Africa and importantly shows the dependence of industrial mining on practices and knowledge developed by African orpailleurs"--